The influence of cold-water immersion on the adaptive response to high-intensity interval training in human skeletal muscle - Broatch, J. (2015)
Despite a lack of understanding of the underlying mechanisms, cold-water immersion (CWI) is extensively used by athletes for recovery. Previous evidence demonstrates its effectiveness in reducing muscle soreness, with the effects on muscle function unclear (260). Given the subjective nature of soreness, the efficacy of post-exercise CWI may be confounded by a potential placebo effect. Debate also exists surrounding the merit of CWI in athletic training regimes. While better recovery may improve subsequent training quality and stimulus (490), there is suggestion that CWI may attenuate long-term skeletal muscle adaptations (523). Conversely, CWI may stimulate the expression of genes key to mitochondrial biogenesis (192). To fully understand the mechanisms underlying CWI, and its influence on athletic performance, it is crucial to investigate these issues further. This thesis firstly aimed to investigate if the placebo effect is responsible for any short-term performance or psychological benefits following post-exercise CWI. To assess this, CWI was compared with a placebo and thermo-neutral control condition in the recovery from a single bout of high-intensity interval training (HIT). A recovery placebo was shown to be superior in the recovery of muscle strength over 48 h as compared with a control, and as effective as CWI, attributed to improved psychological ratings of well-being. This suggests that the placebo effect may account for some of the observed benefits following CWI, or alternately, that it is as strong as the commonly-hypothesised physiological benefits. For the remaining studies, this thesis aimed to investigate the underlying molecular mechanisms by which CWI may alter cellular signalling and the long-term adaptive response to HIT in human skeletal muscle. It was demonstrated that CWI augments the post-exercise response of a number of signalling proteins and genes associated with mitochondrial adaptations. The oxidative stress imposed by CWI may serve to augment p53 activation post-exercise, leading to a greater up-regulation of its downstream targets. However, despite these alterations in cellular signalling, regular post-exercise CWI did not promote an improved adaptive response to HIT, as measured by markers of mitochondrial biogenesis and other aerobic adaptations.